Systematic review of 31P-magnetic resonance spectroscopy studies of brain high energy phosphates and membrane phospholipids in aging and Alzheimer's disease - Jett, Steven; Boneu, Camila; Zarate, Camila; Carlton, Caroline; Kodancha, Vibha; Nerattini, Matilde; Battista, Michael; Pahlajani, Silky; Williams, Schantel; Dyke, Jonathan P.; Mosconi, Lisa (Frontiers in Aging Neuroscience, 2023)
Many lines of evidence suggest that mitochondria have a central role in aging-related neurodegenerative diseases, such as Alzheimer's disease (AD). Mitochondrial dysfunction, cerebral energy dysmetabolism and oxidative damage increase with age, and are early event in AD pathophysiology and may precede amyloid beta (Aβ) plaques. In vivo probes of mitochondrial function and energy metabolism are therefore crucial to characterize the bioenergetic abnormalities underlying AD risk, and their relationship to pathophysiology and cognition. A majority of the research conducted in humans have used 18F-fluoro-deoxygluose (FDG) PET to image cerebral glucose metabolism (CMRglc), but key information regarding oxidative phosphorylation (OXPHOS), the process which generates 90% of the energy for the brain, cannot be assessed with this method. Thus, there is a crucial need for imaging tools to measure mitochondrial processes and OXPHOS in vivo in the human brain. 31Phosphorus-magnetic resonance spectroscopy (31P-MRS) is a non-invasive method which allows for the measurement of OXPHOS-related high-energy phosphates (HEP), including phosphocreatine (PCr), adenosine triphosphate (ATP), and inorganic phosphate (Pi), in addition to potential of hydrogen (pH), as well as components of phospholipid metabolism, such as phosphomonoesters (PMEs) and phosphodiesters (PDEs). Herein, we provide a systematic review of the existing literature utilizing the 31P-MRS methodology during the normal aging process and in patients with mild cognitive impairment (MCI) and AD, with an additional focus on individuals at risk for AD. We discuss the strengths and limitations of the technique, in addition to considering future directions toward validating the use of 31P-MRS measures as biomarkers for the early detection of AD.